'[A] Mere Cloak for their Proud Contempt and Antipathy towards the African Race': Imagining Britain's West India Regiments in the Caribbean, 1795–1838. Issue 4 (4th July 2018) - Lambert, David
ABSTRACT: This article examines opposition to the creation and presence of the West India Regiments in Britain's Caribbean colonies from the establishment of these military units in the mid-to-late 1790s to the formal ending of slavery in the region. Twelve regiments were originally created amid the twin crises associated with Britain's struggle with Revolutionary France and the horrendous losses to disease suffered by British forces in the Caribbean. Their rank-and-file were comprised mainly of men of African descent, most of whom had been bought by the British Army from slave traders or, after the abolition of the British slave trade in 1807, recruited from among people 'liberated' by the Royal Navy. While there was nothing new in using men of African descent, free and enslaved, in the service of the European empires in the Americas, such enrolments had tended to be for fixed or limited periods. Thus, the establishment of the West India Regiments as permanent military units, whose soldiers were uniformed, armed and trained along European lines, was unprecedented—and bitterly opposed by West Indian colonists. Indeed, although white West Indians were concerned about the protection of the colonies from both external and internal foes, they were highly sceptical about whether arming (formerly) enslaved people of African descent would serve to promote their security or might, in fact, imperil the system of racial slavery on which they relied. The tensions arising from the establishment of the West India Regiments have been examined by other historians. However, much of the previous focus has been on the political conflict between the British authorities and local colonial legislatures, and on legal challenges to the regiments, especially during the early years of their existence. In contrast, this article takes a wider view of opposition to the regiments over a longer period up to the formal ending of slavery. In so doing, it examines how the regiments' rank and file were viewed by white West Indians and the deep anxieties this reveals among colonists. The article also considers the efforts made by the regiments' proponents and commanders to promulgate more favourable images of black soldiers, images that became more prominent by the 1830s. The more general argument is that this struggle around how the West India Regiments' rank and file should be viewed was part of a broader 'war of representation' over the image of 'the African' during the age of abolition.